Gut Microbiota as Regulators of Th17/Treg Balance in Patients With Myasthenia Gravis - Chen, Pan; Tang, Xiangqi (Frontiers in Immunology, 2021)
Myasthenia gravis (MG) is an acquired neurological autoimmune disorder characterized by dysfunctional transmission at the neuromuscular junction, with its etiology associated with genetic and environmental factors. Anti-inflammatory regulatory T cells (Tregs) and pro-inflammatory T helper 17 (Th17) cells functionally antagonize each other, and the immune imbalance between them contributes to the pathogenesis of MG. Among the numerous factors influencing the balance of Th17/Treg cells, the gut microbiota have received attention from scholars. Gut microbial dysbiosis and altered microbial metabolites have been seen in patients with MG. Therefore, correcting Th17/Treg imbalances may be a novel therapeutic approach to MG by modifying the gut microbiota. In this review, we initially review the association between Treg/Th17 and the occurrence of MG and subsequently focus on recent findings on alterations of gut microbiota and microbial metabolites in patients with MG. We also explore the effects of gut microbiota on Th17/Treg balance in patients with MG, which may provide a new direction for the prevention and treatment of this disease.